Pendampingan Komunitas Anak Usia Dini Untuk Mengenal Adab Sopan Santun Di Madrasah Diniyah TPQ Al Huda Krajan Desa Wagir Kidul Pulung - Ridho Anfubi; Fuad Fitriawan (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Adab has a very important position in the Islamic religion. Adab can mean attitude, politeness, civilized behavior, good character, improvement of morals, morals, ethics. Adab is something ingrained in humans. Humans who behave well are called civilized humans, while humans who behave badly are called uncivilized humans. In this modern era, many Indonesian people have been found whose behavior does not reflect good manners. Starting from children, teenagers, and even adults. In this community service, the researcher held an activity, namely mentoring the early childhood community to learn good manners at Madrasah Diniyah TPQ Al Huda Krajan, Wagir Kidul Pulung Village, Ponorogo, to produce a generation of young children with good morals. The method used is the ABCD (Asset Based Community Development) method, namely community service which starts from the assets or potential of the community. The result of this community service is that good morals and morals are instilled in children from an early age.